2007
DOI: 10.1128/jvi.00997-07
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Transmission of Immunodeficiency Viruses among Bobcats and Pumas

Abstract: With the exception of human immunodeficiency virus (HIV), which emerged in humans after cross-species transmissions of simian immunodeficiency viruses from nonhuman primates, immunodeficiency viruses of the family Lentiviridae represent species-specific viruses that rarely cross species barriers to infect new hosts. Among the Felidae, numerous immunodeficiency-like lentiviruses have been documented, but only a few cross-species transmissions have been recorded, and these have not been perpetuated in the recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 46 publications
8
81
2
Order By: Relevance
“…All four samples that were equivocal on PLV immunoblot were sequenced and determined to be unique isolates of PLV. All other sequenced PCR products, except for the aforementioned contaminant, were homogeneous with previously described PLV sequences (Carpenter et al, 1996;Franklin et al, 2007). The type of samples used (serum, plasma, or whole blood) did not affect assay results.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…All four samples that were equivocal on PLV immunoblot were sequenced and determined to be unique isolates of PLV. All other sequenced PCR products, except for the aforementioned contaminant, were homogeneous with previously described PLV sequences (Carpenter et al, 1996;Franklin et al, 2007). The type of samples used (serum, plasma, or whole blood) did not affect assay results.…”
Section: Resultsmentioning
confidence: 97%
“…Host-specific lentiviruses have been isolated from numerous nondomesticated felids, including three American species: puma (Puma concolor; Carpenter et al, 1996), bobcat (Lynx rufus; Franklin et al, 2007), and ocelot (Leopardus pardalis; Troyer et al, 2005). Unlike domestic cat feline immunodeficiency virus (FIV), which can cause severe immunosuppression and human immunodeficiency virus (HIV)-like symptoms in felids, lentiviruses of wild felids have not historically been associated with significant pathogenicity (VandeWoude and Apetrei, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…FIV-PcoB infects pumas across most of their range in North and South America, while FIV-PcoA was initially detected only in pumas from Florida (Puma concolor coryii) and southern California (Carpenter et al, 1996;Biek et al, 2003Biek et al, , 2006). An analysis of FIV sequences from bobcats (Lynx rufus) in California (n518) and Florida (n51) demonstrated these isolates cluster with FIV-PcoA (Franklin et al, 2007), suggesting interspecific transmission occurs between bobcats and pumas in these regions. Franklin et al (2007) concluded that FIV-PcoA has coevolved with bobcats and now infects pumas in these two geographic regions due to a ''jump'' from one host to another.…”
Section: Feline Immunodeficiency Virus (Fiv) Is An Enveloped Retrovirmentioning
confidence: 99%
“…An analysis of FIV sequences from bobcats (Lynx rufus) in California (n518) and Florida (n51) demonstrated these isolates cluster with FIV-PcoA (Franklin et al, 2007), suggesting interspecific transmission occurs between bobcats and pumas in these regions. Franklin et al (2007) concluded that FIV-PcoA has coevolved with bobcats and now infects pumas in these two geographic regions due to a ''jump'' from one host to another.…”
Section: Feline Immunodeficiency Virus (Fiv) Is An Enveloped Retrovirmentioning
confidence: 99%
See 1 more Smart Citation